The Effectiveness of Using Google Earth Interactive Media on Geography Learning Outcomes - Riyadi, Sugeng; Arif, Nursida (Journal of Learning Improvement and Lesson Study, 2025)
This study aims to examine the effectiveness of using Google Earth as an interactive medium in geography education, particularly on the topic of the location and physical features of the Earth’s surface. The research was conducted using the Classroom Action Research (CAR) method in two cycles, involving 36 students from class X.E at SMA Negeri 3 Cilacap. Each cycle included learning activities that integrated exploration of Google Earth features to enhance students’ spatial understanding. The results indicated a significant improvement in students’ learning outcomes, with the average score increasing from 64.38 in the pre-cycle to 78.28 in Cycle I, and further rising to 87.39 in Cycle II. Additionally, the percentage of students who met the Minimum Mastery Criteria (KKM) increased from 75% to 94.44%. The use of Google Earth was proven to not only enhance spatial visualization but also to increase student engagement and learning interest. This study confirms that digital geospatial media can serve as an effective learning tool to improve students’ conceptual understanding and spatial thinking skills, while also providing empirical contributions in the context of geography education in developing countries.